Diplomatic Relations between the Rulers of Bukhara and Ottoman Turkish Sultans between the 16th and 19th Centuries (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In this article, the history of the state of Bukhara, one of the most powerful states in Central Asia between the 16th and 19th centuries, is discussed in detail. At the same time, the article describes the political, cultural, economic, military, and trade relations established between the rulers of Bukhara and the Ottoman sultans during this period.